Peningkatan Kesehatan Reproduksi Bagi Wanita Usia Subur Dalam Upaya Pencegahan Ca.Cerviks Di Kelurahan Murni Kecamatan Danau Sipin Jambi - Nurfitriani Nurfitriani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Currently Indonesia is undergoing a change in the pattern of diseases called epidemiological transitions characterized by increased mortality and illness due to non-communicable diseases (PTM) such as stroke, heart disease, diabetes, cancer and others. Cancer is a group of non-communicable diseases caused by growth body cells that are not normal. Cancer is the leading cause of death in the world, and. most cancers experienced by women is cervical cancer. According to experts, cervical cancer is one of the most preventable and treatable types of cancer. Risk factors for cancer include: genetic factors, infectious factors, lifestyle factors, and physical activity factors. Therefore, pre-cancerous lesion screening is very important because the treatment can cure up to 100%. Whereas in invasive cancer, the use of lesions gives less satisfactory results with a life expectancy of 5 years, which is between 20% -90%. Based on field observations and interviews with Posbindu cadres, information was obtained that there were still many mothers who had not done IVA tests, for reasons they did not know, were ashamed and were afraid if they later discovered the type of disease they were suffering from. The target of this activity is the Posbindu group in RT 14 and 15, Kelurahan Murni. Kecamatan Danau Sipin, amounting to 15 people. The purpose of this community service after socialization and health education is able to understand and be motivated and take part in conducting IVA tests. The results obtained with the socialization and health education of post cadre cadre leaders and members and the community increase knowledge and behavior changes.